Implementasi Pengukuran Kasus Bullying Berbasis Gender Dengan Pendekatan Metode Analytic Network Process Dan Structural Equation Modeling - Salma PNua; Sulistiawati Ahmad; Muh Salim (Bulletin of Information Technology (BIT), 2024)
Bullying in the workplace not only has a negative impact on the individual who is the victim, but also has negative consequences for the organization and witnesses who witnessed the incident. The purpose of the study is to describe the psychological aspects related to bullying in the work environment using a valid theoretical conceptual framework. This study combines the Analytical Network Process (ANP) and Structural Equation Modeling (SEM) approaches to investigate the phenomenon of bullying in the work environment with a focus on the gender dimension. The findings suggest that gender has a significant role in influencing the experience of bullying in the workplace, with significant differences between individuals based on their gender. The integrative models of ANP and SEM successfully identified the complexity of the relationship between related variables such as the strength of interpersonal relationships, gender differences, and organizational policies, while also highlighting the negative impact of bullying on individual psychological well-being and organizational productivity. This study shows that all indicators of bullying behavior in the workplace have a p > value of 0.3 based on the results of confirmatory factor analysis. These indicators are threats to professional status (0.591), threats to individuals (0.538), isolating (0.399), excessive workload (0.649), and acts that cause instability (0.310). These results indicate that each of these factors is significant and relevant in measuring bullying behavior in the work environment.